2020
DOI: 10.1021/acsami.0c11739
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-Activated Lysosome Pathway Death Induced by ROS Generated from Layered Double Hydroxide-Copper Sulfide Nanocomposites

Abstract: The overdeveloped lysosomes in cancer cells are gaining increasing attention toward more precise and effective organelle-targeted cancer therapy. It is suggested that rod/platelike nanomaterials with an appropriate size exhibited a greater quantity and longer-term lysosomal enrichment, as the shape plays a notable role in the nanomaterial transmembrane process and subcellular behaviors. Herein, a biodegradable platform based on layered double hydroxide-copper sulfide nanocomposites (LDH-CuS NCs) is successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…As a highly biocompatible family of clay nanomaterials, sheet-like layered double hydroxide (LDH) nanoparticles are extensively explored as a multimodal delivery carrier with the advantages of passive targeting via enhanced penetration and retention (EPR) effect, sheet-like morphology, high loading capacity, and versatile composition. For example, two FDA-approved therapeutics, 5-fluorouracil (5-FU) and siRNA, were integrated into LDH nanosheets for combined chemotherapy and RNAi therapy . Recently, our research demonstrated that effective photothermal conversion of Cu-doped LDH (Cu-LDH) exhibited almost complete tumor inhibition together with chemotherapeutic drug 5-FU .…”
Section: Introductionmentioning
confidence: 99%
“…As a highly biocompatible family of clay nanomaterials, sheet-like layered double hydroxide (LDH) nanoparticles are extensively explored as a multimodal delivery carrier with the advantages of passive targeting via enhanced penetration and retention (EPR) effect, sheet-like morphology, high loading capacity, and versatile composition. For example, two FDA-approved therapeutics, 5-fluorouracil (5-FU) and siRNA, were integrated into LDH nanosheets for combined chemotherapy and RNAi therapy . Recently, our research demonstrated that effective photothermal conversion of Cu-doped LDH (Cu-LDH) exhibited almost complete tumor inhibition together with chemotherapeutic drug 5-FU .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CuS is a well-reported PTA, exhibiting wide absorption range in the NIR window [134]. It was also reported that CuS can produce a huge amount of ROS for PDT upon NIR irradiation, which is realized via the Fenton-like reaction or Haber-Weiss reaction [135,136]. Thus, as promising candidates for phototherapy, CuS combined with immunotherapy can achieve very good immune responses for cancer treatment.…”
Section: 23mentioning
confidence: 99%
“…In recent years, a series of PA-imaging CAs have been developed to improve imaging performance in biomedical applications. For example, biodegradable layered double hydroxide (LDH)-copper sulfide (CuS) nanocomposites were successfully prepared for PA imaging of breast cancer (Figure 1b; Liu, Tang, et al, 2020). Due to the high photothermal conversion efficiency, LDH-CuS NCs not only worked as CAs for PA imaging but also as photothermal agents for PTT under 808-nm laser irradiation.…”
Section: Cu-based Nms Used For Cancer Imagingmentioning
confidence: 99%